(untitled) (Research, Society and Development, 2020)
The objective of this research was to evaluate the microbial and parasitic contamination in lettuce sold in open markets and supermarkets in the city of Mossoró. For parasitological evaluation, spontaneous sedimentation and flotation methods were applied. For the microbiological part, the Most Probable Number (MPM) of total and thermotolerant coliforms was estimated, as well as the positivity of Salmonella sp. Regarding parasitic analysis it was found that the samples had a total index of 62.5% (45/72) of contamination, 40.3% (29/72) with Ancylostomatidae sp., 29.2% (21/72) with Strongyloides sp., 1.4% (1/72) Ascaris sp., 1.4% (1/72) Entamoeba histolytica/dispar, 1.4% (1/72) Endolemax nana, and 2.8% (2/72) Entamoeba coli. For microbiological analyzes, an index of 100% (12/12) of the samples showed contamination by total coliforms and 25% (3/12) of thermotolerant coliforms, above the maximum value allowed by Brazilian legislation, and absence of Salmonella sp. However, there was no difference in microbial and parasitic contamination between the commercial establishments in this research. Finally, the neglect of the lettuce’s hygienic-sanitary conditions by the commercial establishments depicted here is evident, as well as the potential health risk to which the population is exposed.